Development and validation of a voice-hearing task for research on auditory verbal hallucinations and auditory misperception. Issue 4 (2nd October 2017) - Huque, Akib Ul; Heaney, Alice; Poliakoff, Ellen; Brown, Richard J.
Abstract: We developed a brief (5.5 min), continuous voice-hearing task (VHT) to address the limitations of existing paradigms used to study auditory verbal hallucinations in the laboratory. Correlational analysis of VHT data obtained from ordinary participants indicated that false alarm responses on the task were reliable and had convergent and divergent validity. Advantages of the VHT over other similar tasks include its sound psychometric properties, brevity, flexibility, control over confounding factors, suitability for multi-task study, and potential for broader application.